Fixed point theorems for rational type $F$-contraction - Acar, Ö. (Carpathian Mathematical Publications, 2021)
In this paper, we consider rational type $F$-contraction for multivalued integral type mapping on a complete metric space. Using Wardowski’s technique, we establish the existence of a fixed point of the multivalued integral type mapping, if this mapping or the $F$-contraction is continuous. In the end, we give an example which shows that our result is the best.